1984
DOI: 10.3109/01485018409161147
|View full text |Cite
|
Sign up to set email alerts
|

Serum Inhibin Levels after Administration of hCG

Abstract: Administration of hCG to normal healthy men caused 40 fold increase in circulating levels of inhibin at 24 hr. FSH levels decreased between 72-120 hr of hCG injection. Although, testosterone levels were maintained at higher levels during hCG therapy for more than 10 days, inhibin and FSH levels returned back to pretreatment levels, indicating involvement of hCG in the regulation of circulating levels of inhibin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…LHRH increases whereas prolactin (5 pg) and inhibin dramatically suppress FSH synthesis. Increase in biosynthesis of inhibin by hCG in the present study is in agreement with our earlier data in human, whereas hCG administration to human volunteers caused 2/3-fold increase in circulating levels of inhibin [12]. Both prolactin and inhibin suppressed inhibin apart from having similar effect on FSH.…”
Section: Discussionsupporting
confidence: 82%
“…LHRH increases whereas prolactin (5 pg) and inhibin dramatically suppress FSH synthesis. Increase in biosynthesis of inhibin by hCG in the present study is in agreement with our earlier data in human, whereas hCG administration to human volunteers caused 2/3-fold increase in circulating levels of inhibin [12]. Both prolactin and inhibin suppressed inhibin apart from having similar effect on FSH.…”
Section: Discussionsupporting
confidence: 82%
“…Further, the capability of the Leydig cells to synthesize inhibin was evident by the expression of specific mRNA for 32-kDa inhibin [33]. In this context, it was interesting to observe that following HCG administration there is an increase in 10.5-kDa inhibin [21] and 32-kDa inhibin [44] secretion by Leydig cells. A manyfold increase in concentration of 13-kDa inhibin [23] and 32-kDa inhibin [4] in hyperplastic Leydig cells has also been reported.…”
Section: Tissue Distributionmentioning
confidence: 81%
“…Cochran et al found a similar pattern in their studies of HCG secreting testicular tumors.32 High levels of both endogenous and exogenous HCG can result in Leydig cell stimulation which can be manifested histologically as Leydig cell hyperplasia and biochemically as increased serum estradiol relative to te~tosterone.~'-~~ Administration of HCG to normal, healthy men has been shown to result in a dramatic increase in circulating levels of serum inhibin and a concomitant, although transient, depression in FSH. 35 Another patient had a similar pattern of gonadotropin release, but normal HCG and testosterone levels. Estradiol was not measured and isolated elevation of this hormone would have been expected to produce a decrease in serum LH.36 One patient had a hormone profile consistent with hypergonadotropic hypogonadism.…”
Section: Methodsmentioning
confidence: 94%